Okay so here's the the problem:

Let $k \in \mathbb{Z}.$ Then, $\forall$ $m \in [1,k]$, $$f^{(m)}(x) = \sum_{n=1}^\infty{[a_ncos(nx)]^{(m)}+[b_nsin(nx)]^{(m)}} \leq \sum_{n=1}^\infty{(|a_nn^m| + |b_nn^m|)}$$

Now I'm not sure really sure how to approach this. A friend of mine asked me for some aid with this, saying to use the "Differentiation Theorem of a function" from Rudin's text. I really wasn't sure which Differentiation Theorem he was speaking of and trying to dig deeper, he said that's all he knew on the way to approach this. I tried looking at Lebesgue's Differentiation Theorem but it seemed far too complicated for this problem. My friend supplied me with a Theorem and its corollary that lead to the proposition:

Theorem: If $f$ is a periodic function with Fourier coefficients $a_n,b_n$ and the series $\sum_{n=1}^\infty(|a_nn^k|+|b_nn^k|)$ converges for some $k \in \mathbb{N}$, then $f$ has continuous derivatives $f',f'',...,f^{(m)}$

Corollary: Let $k \in \mathbb{N}$. If $f$ is periodic, with Fourier coefficients $a_n,b_n$ and the series $\sum_{n=1}^\infty{(|a_n| + |b_n|)|n^k|}$ converges for some $k$, then $\forall$ $m \in [0,k]$ it follows that $$f^{(m)}(x)=\frac{d^m}{dx^m}[a_0+\sum_{n=1}^\infty({a_ncos(nx)+b_nsin(nx)})] $$

The proposition clearly sets up an inequality between the Theorem and its Corollary. I'm just quite unsure where to go with this. If anyone could give a hand, my friend and I would be much obliged.


Thanks to Michael Albanese, I think I've got the answer now. Here is my attempt at a formal proof

Proposition: Prove $\forall$ $m \in [1,k]$, where $k \in \mathbb{N}$, that $$\frac{d^m}{dx^m}(\sum_{n=1}^\infty(a_ncos(nx)+b_nsin(nx))) \leq \sum_{n=1}^\infty(|a_nn^m|+|b_nn^m|)$$


Consider $\mathbb{Z_4}$, where we have equivalence classes $[0]_4,[1]_4,[2]_4,[3]_4$. Now observe that $\forall$ $m \in [1,k]$ $$\frac{d^m}{dx^m}(cos(nx))=\left\{ \begin{array}{lr} n^mcos(nx) & m\equiv [0]_4\\ -n^msin(nx) & m\equiv [1]_4\\ -n^mcos(nx) &m\equiv [2]_4\\ n^msin(nx) &m\equiv [3]_4 \end{array} \right.$$

$$\frac{d^m}{dx^m}(sin(nx))=\left\{ \begin{array}{lr} n^msin(nx) & m\equiv [0]_4\\ n^mcos(nx) & m\equiv [1]_4\\ -n^msin(nx) &m\equiv [2]_4\\ -n^mcos(nx) &m\equiv [3]_4 \end{array} \right.$$


$$\frac{d^m}{dx^m}(cos(nx)) \leq \bigl|\frac{d^m}{dx^m}(cos(nx))\bigr|=\left\{ \begin{array}{lr} |n^mcos(nx)| & m\equiv [0]_4\\ |n^msin(nx)| & m\equiv [1]_4\\ |n^mcos(nx)| &m\equiv [2]_4\\ |n^msin(nx)| &m\equiv [3]_4 \end{array} \right. $$ $$\frac{d^m}{dx^m}(sin(nx)) \leq \bigl|\frac{d^m}{dx^m}(sin(nx))\bigr|=\left\{ \begin{array}{lr} |n^msin(nx)| & m\equiv [0]_4\\ |n^mcos(nx)| & m\equiv [1]_4\\ |n^msin(nx)| &m\equiv [2]_4\\ |n^mcos(nx)| &m\equiv [3]_4 \end{array} \right.$$

Recall now that $\bigl|cos(x)\bigr| \leq 1$ and $\bigl|sin(x)\bigr| \leq 1$ which extends to $nx$. Thus,

$$\bigl|\frac{d^m}{dx^m}(cos(nx))\bigr| \leq \left\{ \begin{array}{lr} |n^m| & m\equiv [0]_4\\ |n^m| & m\equiv [1]_4\\ |n^m| &m\equiv [2]_4\\ |n^m| &m\equiv [3]_4 \end{array} \right. \equiv |n^m|$$ $$\bigl|\frac{d^m}{dx^m}(sin(nx))\bigr| \leq \left\{ \begin{array}{lr} |n^m| & m\equiv [0]_4\\ |n^m| & m\equiv [1]_4\\ |n^m| &m\equiv [2]_4\\ |n^m| &m\equiv [3]_4 \end{array} \right. \equiv |n^m|$$

since for both $\bigl|\frac{d^m}{dx^m}(cos(nx))\bigr|$ and $\bigl|\frac{d^m}{dx^m}(sin(nx))\bigr|$, we see our last inequalities result in $|n^m|$ for $[0]_4,[1]_4,[2]_4,[3]_4$. Therefore, it follows that

$$\frac{d^m}{dx^m}(\sum_{n=1}^\infty(a_ncos(nx)+b_nsin(nx))) = \sum_{n=1}^\infty(a_n\frac{d^m}{dx^m}((cos(nx))+b_n\frac{d^m}{dx^m}((sin(nx)))$$ $$\leq \bigl|\sum_{n=1}^\infty (a_n\frac{d^m}{dx^m}((cos(nx))+b_n\frac{d^m}{dx^m}((sin(nx))\bigr)|$$ $$\leq \sum_{n=1}^\infty (\bigl|a_n\frac{d^m}{dx^m}((cos(nx))+|b_n\frac{d^m}{dx^m}((sin(nx))\bigr|)$$

$$\leq \sum_{n=1}^\infty (\bigl|a_n\frac{d^m}{dx^m}((cos(nx))\bigr|+\bigl|b_n\frac{d^m}{dx^m}((sin(nx))\bigr|)$$ $$\leq \sum_{n=1}^\infty(|a_nn^m|+|b_nn^m|)$$

$$\implies \frac{d^m}{dx^m}(\sum_{n=1}^\infty(a_ncos(nx)+b_nsin(nx))) \leq \sum_{n=1}^\infty(|a_nn^m|+|b_nn^m|)$$ $$\blacksquare$$


Hint: $$\frac{d^m}{dx^m}\cos(nx) = \begin{cases} n^m\cos(nx) & m \equiv 0 \bmod 4\\ -n^m\sin(nx) & m \equiv 1 \bmod 4\\ -n^m\cos(nx) & m \equiv 2 \bmod 4\\ n^m\sin(nx) & m \equiv 3 \bmod 4. \end{cases}$$

Now use the fact that $|\cos(nx)| \leq 1$ and $|\sin(nx)| \leq 1$.

  • $\begingroup$ Oh my. So then showing a similar thing for sin(nx), we can then successfully set up our inequality. So we don't need to make any reference to the "Differentiation Theorem of a function"? $\endgroup$ – user30625 Jun 13 '14 at 4:07
  • $\begingroup$ No you don't. I have no idea what your friend meant by that. $\endgroup$ – Michael Albanese Jun 13 '14 at 4:10
  • $\begingroup$ Alright I finally finished typing up my proof in Latex. It's long, but if you're willing to check it, it'd be of much help to me to know that I was on the right the right path. I'm going to put it in the original post. $\endgroup$ – user30625 Jun 13 '14 at 6:07
  • $\begingroup$ Looks pretty good to me. $\endgroup$ – Michael Albanese Jun 13 '14 at 6:25

Your Answer

By clicking “Post Your Answer”, you agree to our terms of service, privacy policy and cookie policy

Not the answer you're looking for? Browse other questions tagged or ask your own question.